Inflammation-mediated effects of diabetes mellitus on male fertility: a systematic review and meta-analysis - Hao, Yanan; Yang, Zheng; Feng, Yanni; Zhao, Yong; Ren, Yonglin (Frontiers in Endocrinology, 2025)
BackgroundDiabetes mellitus (DM) has emerged as a rapidly growing global health problem, imposing substantial socioeconomic burdens and multidimensional health consequences, including adverse effects on male fertility. Although accumulating evidence suggests associations between DM and male reproductive dysfunction, comprehensive mechanistic insights, particularly through inflammatory pathways, remain inadequately elucidated.MethodWe conducted a systematic literature search on Web of Science, Embase, and PubMed databases (1972–2022) to investigate DM-related male infertility through meta-analysis. Following PRISMA guidelines, eight of 168 studies on type 1 diabetes (T1D) and nine of 185 studies on type 2 diabetes (T2D) were included to screen the relationship between diabetes and male infertility. In addition, 10 of 840 inflammation-related studies (1961–2022) underwent rigorous selection for mechanistic exploration. Meta-analysis was conducted to evaluate the summary relative risk (RR) and 95% confidence intervals (CIs) across the combined studies.ResultsMeta-analysis demonstrated a significant impairment of male fertility in diabetic populations. Subgroup analyses revealed that T2D is more likely to cause male infertility compared to T1D. Despite low between-study heterogeneity, inflammation biomarkers (e.g., TNF-α) were implicated in diabetes-induced male infertility. Transcriptomic analyses further identified enriched inflammatory pathways and altered expression of fertility-related genes.ConclusionCurrent evidence indicates that diabetes adversely affects male fertility through inflammatory pathways.